How is the Old Testament Law “Weak”? - Averbeck, Richard E. (HIPHIL Novum, 2024)
The Old Testament law is holy, righteous, good, and spiritual (Rom 7:12, 14), but it is also weak because it cannot work in a human heart to make a person spiritual (Rom 7:14 with 8:3). No law can change a human heart, not even God’s law. The tenth commandment is an example (Rom 7:7–8): The command not to covet cannot stop the sinful human heart from coveting, but incites it to covet all the more. We remain all tangled up in our sin as long as we continue to depend on the human law for strength (Rom 7:14–25). But God has set us free from that enslavement to sin through the work of Christ (Rom 8:1), and enables us to live free in Christ by the power of the work of the Holy Spirit in our human spirit (Rom 8:4–16). We can live now by the Spirit who works a “spirit of adoption” rather than a spirit of slavery within us. The spirit of adoption works God’s love deeply within us so that we become more and more convinced of it and live out of the knowledge that nothing can ever separate us from the love of God.